2015
DOI: 10.1186/s12991-015-0087-6
|View full text |Cite
|
Sign up to set email alerts
|

The characteristics of the suicide attempter according to the onset time of the suicidal ideation

Abstract: ObjectiveTo determine the timing of development of suicidal ideation and factors associated therewith in suicide attempters who required psychiatric emergency treatment.MethodsOf a total of 2818 suicide attempters in Japan who presented to the primary or secondary emergency department of Iwate Medical University Hospital (hereinafter, referred to as our hospital) or Iwate Prefecture Advanced Emergency and Critical Care Center (hereinafter, referred to as the emergency center), an affiliated institution to our … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
1
1
0
Order By: Relevance
“…This reflects the characteristics previously described in other studies on those who attempt suicide [ 36 , 37 ]. The main mode utilized by our sample was the ingestion of drugs, which is also consistent with previous reports [ 38 , 39 ]. However, while 45% of relevant studies described a wide range of alcohol consumption (10 to 73%), a meta-analysis in 2004 identified a mean of 40% [ 40 ], which is again similar to earlier reports from our hospital [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…This reflects the characteristics previously described in other studies on those who attempt suicide [ 36 , 37 ]. The main mode utilized by our sample was the ingestion of drugs, which is also consistent with previous reports [ 38 , 39 ]. However, while 45% of relevant studies described a wide range of alcohol consumption (10 to 73%), a meta-analysis in 2004 identified a mean of 40% [ 40 ], which is again similar to earlier reports from our hospital [ 41 ].…”
Section: Discussionsupporting
confidence: 91%
“…Various kinds of interventions were specifically designed to address problems identified by the Police and CSRP. Research has shown that suicide attempters, people with self‐harm behaviors, and suicide survivors have higher subsequent risk of suicide (Otsuka et al, 2015; Stallard et al, 2013; Young et al, 2012). This was the driver for the three‐pronged intervention, targeting indicated risk (individual), selective risk (at‐risk subgroups), and universal risk (whole population) (World Health Organziation, 2019; Yip, 2005).…”
Section: Discussionmentioning
confidence: 99%